Deteksi Keberadaan Penyebab Penyakit Citrus Vein Phloem Degeneration (CVPD) pada Tanaman Jeruk dengan Gejala Menyeluruh Menggunakan Teknik Polymerase Chain Reaction (PCR) - SITORUS, OCTA FRANSISCA; WIJAYA, I NYOMAN; PUSPAWATI, NI MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2016)
Detection of Ocurrence Citrus Vein Phloem Degeneration (CVPD) Disease on Citrus Plant with Comprehensive Symptoms using Polymerase Chain Reaction (PCR) Technique Citrus Vein Phloem Degeneration (CVPD) is one of very serious disease of citrus plant. The disease is caused by Liberobacter asiaticum bacteria and transmitted by Diaphorina citri Kuw insect. The outspread of disease can also caused by the use of citrus seedlings which have been infected by CVPD. Preliminary visual observations CVPD disease symptoms, there are two types of plants showing symptoms of partial and systemic. Partial symptoms are not all the leaves of plants showing symptoms CVPD, while the systemic symptom is on the whole leaves of plants showing symptoms CVPD. This research aimed to determine the outspread of L. asiaticum bacteria in every parts of the plant that made detection by PCR. The research has been conducted from in Batukaang, Bangli and Plaga, Badung then continued at Laboratory of Genetic Resources and Biology Molecular, Udayana University. Results of PCR visualization using 1% agarose gel showed that there were a DNA band at 1160 bp on the leaves, twigs, branches and trunks. Because the size of 1160 bp DNA bands is expression by L. asiaticum , then the citrus leaf samples were detected positive for the L. asiaticum and it can be ascertained that L. asiaticum haas been distributed to all parts of the plant.
Keywords: Citrus; CVPD; L. asiaticum; PCR